Never forget Mao: the monumental as radical universal or: the making of a “Maoist modern” - Mittler, Barbara (Art and modernism in socialist China, 2024)
In socialist countries like China, monuments of political icons are ubiquitous and universal, and artists cannot avoid engaging with the monumental style. Yet, how to deal with the socialist hero once he dies and falls from grace? Stalin’s statues are dismantled in a series of dramatic performances, and Chiang Kai-shek’s are relegated to large memorial parks. Mao’s, on the other hand, have started to grow - in numbers, size, material variety and social use - and thus have become ever more visible, tangible, sensible and tactile. The period in which monumental Mao played a significant role is not so easily forgotten in China, as it continues right down to the present. This is so because it was not exclusively determined by “socialist realism,” not only “bleak” and “monolithic,” but much more. - Indeed, the chapter argues that Monumental Mao, or the Maoist Modern, must be considered to dominate the long twentieth century, and certainly not just within China. It takes in many elements, with “socialist realism” being just one of them. The Maoist Modern even contains the global artistic exchanges that are the focus of this volume. Accordingly, the chapter addresses not just the question of “socialist realism” but the very meaning of “modernism” itself.
Gesehen am 06.03.2025